Water-resistant gypsum expanded-clay concrete technology. Issue 3 (June 2020) - Panchenko, Alexander; Kharchenko, Igor
Abstract: The results of studies on the technology of preparation and hardening of the expanded-clay concrete under various conditions, prepared on the basis of a water-resistance complex gypsum binder (CGB), are presented. It is shown that CGB-based expanded-clay concrete can be used to erect the outer walls of residential and civil buildings. The optimal preparation methods and temperature and humidity conditions for hardening water-resistance CGB-based expanded-clay concrete are given.